2020
DOI: 10.3390/ijms21144950
|View full text |Cite
|
Sign up to set email alerts
|

Kaolin Reduces ABA Biosynthesis through the Inhibition of Neoxanthin Synthesis in Grapevines under Water Deficit

Abstract: In many viticulture regions, multiple summer stresses are occurring with increased frequency and severity because of warming trends. Kaolin-based particle film technology is a technique that can mitigate the negative effects of intense and/or prolonged drought on grapevine physiology. Although a primary mechanism of action of kaolin is the increase of radiation reflection, some indirect effects are the protection of canopy functionality and faster stress recovery by abscisic acid (ABA) regulation. The physiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 42 publications
2
23
2
Order By: Relevance
“…In 'Douro', VvNCED gene expression was upregulated in kaolin-treated leaves during the 2017 growing season, particularly in the TF variety, but not in the following growing season; this suggests a different varietal sensitivity for ABA synthesis and regulation with kaolin treatment, which seems higher in TF under conditions of intense summer stress. Interestingly, despite the sharp VvNCED upregulation found in treated vines, particularly in TF, ABA accumulation did not change significantly, contrasting with the results of Dinis et al (2018a) and Frioni et al (2020), who reported a reduction in ABA content in kaolin-treated grapevines under summer and water stress conditions.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…In 'Douro', VvNCED gene expression was upregulated in kaolin-treated leaves during the 2017 growing season, particularly in the TF variety, but not in the following growing season; this suggests a different varietal sensitivity for ABA synthesis and regulation with kaolin treatment, which seems higher in TF under conditions of intense summer stress. Interestingly, despite the sharp VvNCED upregulation found in treated vines, particularly in TF, ABA accumulation did not change significantly, contrasting with the results of Dinis et al (2018a) and Frioni et al (2020), who reported a reduction in ABA content in kaolin-treated grapevines under summer and water stress conditions.…”
Section: Discussioncontrasting
confidence: 95%
“…In 2018, most VvNCED genes were down-regulated in treated grapevines in both locations, supporting the hypothesis that acclimated plants can limit nonessential cellular responses under moderate stress conditions (Larkindale and Vierling, 2008). The decreased expression of VvNCED genes in kaolintreated plants might also be due to changes in the upstream pathway of ABA synthesis in leaves, involving carotenoid metabolism and xanthophyll cycle activation, which play an essential role in protecting plants against water deficit as recently demonstrated by Frioni et al (2020). Regarding the effects of kaolin in terms of triggering ABAresponsive gene expression, the results showed that VvHVA22a, and VvSnRK2.6 were down-regulated in TN in both regions and sampling years ( Figure 5), possibly related to lower ABA levels ( Figure 3), suggesting reduced ABA-dependent plant development (Brands, 2002;Kulik et al, 2011).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In vascular plants, it regulates a multitude of physiological processes like seed and bud dormancy [ 11 ], cambium activity [ 12 ], organs development [ 13 ], and fruit ripening [ 14 ]. Yet, it is involved in mediating physiological responses to stressful conditions, especially excessive temperature, salinity, and drought [ 15 , 16 , 17 , 18 ]. ABA has been mainly investigated as it promotes the loss of turgor pressure in guard cells triggering stomatal closure [ 9 ], however, an increasing amount of evidences, also based on V. vinifera , address to ABA a central role in other fundamental processes as the hydraulic response to prolonged drought conditions [ 19 ], the regulation of carbohydrate metabolism during recovery [ 20 ], and the exclusion of excessive salts dissolved in the soil solution [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The reviews published in this issue focus on the interaction between ABA and GAs in regulating non climacteric fruit development and maturation [ 7 ], current knowledge on the role of ABA in mediating mechanisms whereby grapevine deals with abiotic stresses [ 8 ], the analysis of the role of ABA in flowering transition [ 9 ], the mechanism by which the type 2C Protein Phosphatases (PP2C) gene transcription modulates ABA signaling [ 10 ], and the role of the Mediator complex on the ABA signaling pathway and abiotic stress response [ 11 ]. The original research articles investigate the causes and consequences of the kaolin-induced modulation of ABA biosynthesis in grapevines when faced with a water deficit [ 12 ], the involvement of ABA in plant immune responses [ 13 ], and the relation between GAs and Arabidopsis receptor-like cytoplasmic kinase (RLCK) VI_A2 [ 14 ]. In this editorial, I summarize the main findings of these eight insightful works.…”
mentioning
confidence: 99%